2022
DOI: 10.48550/arxiv.2207.00275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local manifold learning and its link to domain-based physics knowledge

Abstract: In many reacting flow systems, the thermo-chemical state-space is known or assumed to evolve close to a low-dimensional manifold (LDM). Various approaches are available to obtain those manifolds and subsequently express the original high-dimensional space with fewer parameterizing variables. Principal component analysis (PCA) is one of the dimensionality reduction methods that can be used to obtain LDMs. PCA does not make prior assumptions about the parameterizing variables and retrieves them empirically from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Local Principal Component Analysis (LPCA) is a dimensionality reduction technique, proposed by Kambhatla et al [37], based on the projection of high-dimensional data onto k sets of lower-dimensional manifolds. Although this algorithm was originally proposed for dimensionality reduction, it has been frequently utilized for clustering tasks in the last years [38][39][40][41]. In addition, it has been shown that, when applied to reacting flow databases, LPCA can ensure a better partitioning with respect to popular unsupervised algorithms such as k-Means and Self-Organzing Maps (SOMs) [32].…”
Section: Clustering Via Local Principal Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Local Principal Component Analysis (LPCA) is a dimensionality reduction technique, proposed by Kambhatla et al [37], based on the projection of high-dimensional data onto k sets of lower-dimensional manifolds. Although this algorithm was originally proposed for dimensionality reduction, it has been frequently utilized for clustering tasks in the last years [38][39][40][41]. In addition, it has been shown that, when applied to reacting flow databases, LPCA can ensure a better partitioning with respect to popular unsupervised algorithms such as k-Means and Self-Organzing Maps (SOMs) [32].…”
Section: Clustering Via Local Principal Component Analysismentioning
confidence: 99%
“…• Initialization: the clusters' centers of mass (centroids) Additional information on the PCA decomposition and reconstruction error, as well as the on LPCA partitioning algorithm, can be found in [38][39][40][41].…”
Section: Clustering Via Local Principal Component Analysismentioning
confidence: 99%